PENGARUH EKSTRAK BAWANG MERAH (Eleutherina americana) DENGAN MADU PADA MINUMAN FUNGSIONAL - Ningrum Hastuti Hastuti; Refid Ruhibnur (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2016)
Dayak onion also called onion Mecca (Eleutherine americana) is a typical plant in Central Kalimantan. This plant has been handed down Dayak community is used as a medicinal plant. Dayak onion processing into refined products it needs to be developed considering the sale of higher value than the fresh form. The purpose of this study was to determine the content of the antioxidant in onions Mecca and determine the best treatment combination between Mecca onion extract and honey to create chemically functional beverages and organoleptic tests. This study uses a Single randomized design with LSD 5% on chemical parameters during boiling of 0, 5, 10, 15 and 20 minutes. Measurement of organoleptic test on color, flavor, and aroma using friedman test. The results showed that the highest antioxidant levels obtained during boiling 10 minutes amounted to 55.79% and the lowest in the boiling water for 0 minutes at 12.82%. The best treatment is a combination of chemicals found at boiling for 10 minutes with antioxidants kada of 55.79% and total phenolic amounted to 4514.70 mg/g, whereas the best treatment combination on organoleptic test was obtained from a combination of onions mekah treatment that has been boiled for 10 minutes with the addition of 15 ml honey with a value of 5.05 (flavor), 7.60 (color), and 7.45 (aroma).Keywords: mecca onion extract, honey, functional drinks